EOLES Course – Five Years of Remote Learning and Experimenting - Fidalgo, André (2021)
The EOLES (Electronics and Optics e-Learning for Embedded Systems) course consists of a 3rd year Bachelor degree that relies exclusively on e-learning and remote laboratories, developed as the result of an EU funded ERASMUS+ project, involving 15 institutions from four European and three North African countries and concluded in 2015. This paper presents an overview and overall results for this initial period and a more detailed analysis of the Digital Systems Teaching Unit contents, pedagogical approach, grading methodology and results. The focus is on the unit specific characteristics and features, student and teacher experiences and the methodologies that were applied to enhance learning success. The Teaching Unit expositive material is provided as the student progresses, with progressive unlocking of content depending timeline and automatic quizzes results. Grading is divided between weekly assignments, an online exam at the end of each TU and a final exam at the end of the academic year. In short, students are allowed and encouraged to adjust their learning rhythm within the limits allowed by time restraints and evaluation criteria. The developed course was accredited as a specialization year in most partner institutions and has been running non-stop since then, mainly with students from North African institutions. Although no longer supported by an EU project, the course is a good example of sustainability as it already had 4 effective editions with successful approval rates and always with many more candidates than available vacancies.